Preparing pre-service teachers for integration of education for sustainable development in school : a systematic review (2013-2022) - Farah Izyan Raman,; Fonny Dameaty Hutagalung,; Mohd Nazri Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Teacher education is accountable for ensuring that all students acquire the knowledge and skills required to promote sustainable development, primarily via education for sustainable development (ESD). However, most of the research on ESD in teacher education focuses on specific education courses and countries. Thus, this review systematically explores global trends in ESD research within teacher education. Based on two databases, Web of Science and Scopus, 27 publications were retrieved from 2013 to 2022 using the SLR methodology and further analysed using the PRISMA method to obtain the main themes. First, the significant findings portrayed that ESD integration does not have any boundaries between fields. Second, the evidence demonstrates that ESD is integrated using various expanding strategies and methods into teacher education across nations and programmes. Third, by understanding the existence of various variables, actions and measurements may be performed before or after the incorporation of ESD into teacher education curricula in connection to the availability of external factors that may impact ESD implementation. These three findings indicated that there are still research gaps concerning ESD in teacher education to be explored. In conclusion, this study is beneficial for practitioners in evaluating which ESD approach is currently being used and in identifying ESD-related research needs in teacher education. In order to achieve the Sustainable Development Goals (SDGs) by 2030, the enhancement of ESD in teacher training institutions might lead to a new vision of education.